2017
DOI: 10.1016/j.cej.2017.05.177
|View full text |Cite
|
Sign up to set email alerts
|

CO2 dissociation in a packed bed DBD reactor: First steps towards a better understanding of plasma catalysis

Abstract: Plasma catalysis is gaining increasing interest for CO2 conversion, but the interaction between the plasma and catalyst is still poorly understood. This is caused by limited systematic materials research, since most works combine a plasma with commercial supported catalysts and packings. In the present paper, we study the influence of specific material and reactor properties, as well as reactor/bead configuration, on the conversion and energy efficiency of CO2 dissociation in a packed bed dielectric barrier di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(163 citation statements)
references
References 81 publications
5
156
2
Order By: Relevance
“…The reactor was chosen because of its large volume, which facilitates diagnostic measurements. Furthermore, the reactor does not require packing with catalyst or inert particles, and thus complicated interactions with the bed, which obfuscate fundamental interpretations of reaction rates, were avoided . It will be demonstrated that the steady state is nominally independent of the initial feed speciation provided the relative amounts of different elements are held constant, and that superlocal equilibrium state is fundamentally different than the local equilibrium state at the background temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The reactor was chosen because of its large volume, which facilitates diagnostic measurements. Furthermore, the reactor does not require packing with catalyst or inert particles, and thus complicated interactions with the bed, which obfuscate fundamental interpretations of reaction rates, were avoided . It will be demonstrated that the steady state is nominally independent of the initial feed speciation provided the relative amounts of different elements are held constant, and that superlocal equilibrium state is fundamentally different than the local equilibrium state at the background temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the catalysts in the form of particle rather than powder are favored to ensure smooth airflow in the reactor. Capacity of coaxial DBD reactor can be improved by tube array structure, or enlarging the size of inner and outer electrodes to increase the catalyst volume . However, the discharge properties may be altered significantly.…”
Section: Discharge Types Of Ap Cold Plasmamentioning
confidence: 99%
“…Reactions (4) and (5) yield the dissociation of CO 2 and H 2 O, but the products, CO and OH, will rapidly recombine into CO 2 again (reaction (6)). Moreover, the two H atoms and one O atom formed will also quickly recombine, first into OH (through subsequent reactions (7) and (8)) and subsequently into H 2 O through reaction (9). Thus, overall, there is no net dissociation of CO 2 and H 2 O in this pathway (see overall reaction (10)).…”
Section: Co 2 /H 2 O Mixturementioning
confidence: 99%
“…As our results indicate that a higher dielectric constant constrains the discharge to the contact points of the beads, this may limit the catalyst activation due to the limited catalyst surface area in contact with the discharge, and thus it may have implications for the efficiency of plasma catalytic CO 2 conversion. Indeed, the best results are not always reached for the highest dielectric constant [9,10]. Figure 11 illustrates a typical 3D gas flow pattern (a), as well as the calculated electron density profile (b), in a reverse vortex flow (RVF) GA plasma reactor, also called gliding arc plasmatron (GAP), operating in argon.…”
Section: Packed Bed Dbd Reactorsmentioning
confidence: 99%
See 1 more Smart Citation